2018
DOI: 10.1038/s41417-018-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological implications of mutational spectrum in acute myeloid leukemia of FAB subtypes M4 and M5

Abstract: The mutational spectrum and molecular characteristics of acute myelomonocytic lineage leukemia, namely acute myeloid leukemia (AML) French-American-British (FAB) subtypes M4 and M5, are largely unknown. In order to explore the mutational spectrum and prognostic factors of FAB-M4 and -M5, next-generation sequencing (NGS) was performed to screen for mutated genes and fusion genes relevant to the pathogenesis of AML. Of the 63 patients enrolled in the study, 60% had more than three mutated genes. NPM1 had the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…Multivariate analysis of the chemotherapy‐only group was consistent with previous studies in that older age (≥60 years), more BM blasts (≥70%), mutations in TP53 and DNMT3A also independently contributed to shorter EFS and OS . The effect of high DDIT4 expression on survival was not reproduced in the allo‐HSCT group, whereas WBC count ≥ 15 × 10 9 /L, FLT3‐ITD and TP53 mutation were associated with poor OS or EFS, suggesting that allo‐HSCT could ameliorate the adverse prognostic effect of high DDIT4 expression in AML.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Multivariate analysis of the chemotherapy‐only group was consistent with previous studies in that older age (≥60 years), more BM blasts (≥70%), mutations in TP53 and DNMT3A also independently contributed to shorter EFS and OS . The effect of high DDIT4 expression on survival was not reproduced in the allo‐HSCT group, whereas WBC count ≥ 15 × 10 9 /L, FLT3‐ITD and TP53 mutation were associated with poor OS or EFS, suggesting that allo‐HSCT could ameliorate the adverse prognostic effect of high DDIT4 expression in AML.…”
Section: Discussionsupporting
confidence: 83%
“…Multivariate analysis of the chemotherapy-only group was consistent with previous studies in that older age (≥60 years), more BM blasts (≥70%), mutations in TP53 and DNMT3A also independently contributed to shorter EFS and OS. [25][26][27][28] To summarize, our results indicated that enhanced DDIT4 expression could be a poor prognostic factor for AML patients treated with chemotherapy alone, and these patients might benefit from allo-HSCT. We were able to identify a unique gene expression pattern and cell signalling pathways associated with DDIT4 expression, which could shed lights on the role of DDIT4 in leukaemogenesis.…”
Section: Chemotherapy-only Groupmentioning
confidence: 63%
“…Multivariate analysis indicated that in the chemotherapy-only group, age ≥60 years, BM blasts ≥70%, and WBC count ≥15 × 10 9 /L also independently contribute to poor survival. This is concordant with older studies that older age confers unfavorable prognosis in AML, possibly due to higher mutation burden, lower baseline performance status and more co-morbidities in this population (23). The deleterious effects of highly-active bone marrow blast proliferation and high peripheral WBC count on AML remission rate and survival are also well described in previous findings that they have adverse effect on OS (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…Some of the studies suggested that higher IDO expression is observed in the FAB-M5 subtype (19,30,31). The FAB-M5 subtype is associated with leukemia derived from a myelomonocytic lineage (38), and as aforementioned, IDO expression on mononuclear cells, including monocytes and monocyte-derived DCs has been found. As FAB-M5 is leukemia of monocytic origin and IDO can be expressed by these cells, it could account for this correlation.…”
Section: Discussionmentioning
confidence: 92%